Parallel Parking System Design with Fuzzy Logic Control - Mochamad Irwan Nari; Zainul Mustain; Syamsiar Kautsar; Satryo Budi Utomo (Jurusan Teknik Elektro Universitas Andalas, 2021)
The difficulty with parallel parking, especially when going backwards is when adjusting the steering wheel so that the car can park in the right direction. Based on these problems, this study aims to design an automatic parking system. To improve parking success, a trajectory tracking system with fuzzy logic control will be implemented on a 1/7.5 scale test car. The coordinates obtained from the bicycle kinematic model are compared with the design trajectory. The difference between the facing direction read by the gyroscope sensor and the trajectory design is processed using a fuzzy logic controller to direct the servo motor as the steering wheel. The test results obtained that the error value for the position and direction facing in the automatic parking test using fuzzy logic control is 1.25cm and 1.59°.Keywords: Trajectory tracking, gyroscope, fuzzy logic control, parallel parking